Study of the Relationship between CA 15.3 Levels and C - reactive protein (CRP) in Breast Carcinoma after Chemotherapy and its Relation to Clinical and Pathological Characteristics (Journal of Medical Sciences, 2023)
Breast cancer is one of the invasive and most frequent cancers and the second cause of death in women in the world. This study aimed to estimate the levels of CA15.3 protein and C-reactive protein (CRP) in breast cancer patients who attending to the Sebha Oncology Centre and to study the relationship between them, as well as to study the relationship between signs and characteristics. The clinical study of patients and the study were conducted on 46 women, including 23 women with breast cancer who attended the Centre, and 23 women Healthy volunteers, whichwere taken as a control group. The results obtained after statistical analysis showed that the highest infection rate was in the age group of 41-50 yearsa rate of 60.86%. The level of CA15.3 protein was measured using the Cobas E411 device, and the results of the T test for the levels of CA15.3 protein were at the level of significance P